Mutants of Escherichia coli Sensitive to Antibiotics - Ennis, Herbert L. (1971)
Mutants of Escherichia coli sensitive to the antibiotic synergistin A, an inhibitor of protein synthesis, were isolated. These mutants were pleiotropic, being also sensitive to a large number of unrelated antibiotics and to lysis by detergents. These pleiotropic responses indicated that the mutations affected cell wall or membrane synthesis. Consequently, selection for antibiotic-sensitive mutants constitutes a useful means for isolating cell wall or membrane mutants.